2023
DOI: 10.3389/fpls.2023.1251441
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting establishment and population growth of the invasive weed Ambrosia artemisiifolia

Wenxuan Zhao,
Zhifang Xue,
Tong Liu
et al.

Abstract: Ambrosia artemisiifolia is a highly invasive weed. Identifying the characteristics and the factors influencing its establishment and population growth may help to identify high invasion risk areas and facilitate monitoring and prevention efforts. Six typical habitats: river banks, forests, road margins, farmlands, grasslands, and wastelands, were selected from the main distribution areas of A. artemisiifolia in the Yili Valley, China. Six propagule quantities of A. artemisiifolia at 1, 5, 10, 20, 50, and 100 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
1
0
0
Order By: Relevance
“…In the invasive species Ambrosia artemisiifolia which reacts favourably to a warmer climate, the earlier onset of flowering is related to precipitation pre-season, in the period from sprouting to pollen maturation. This is in line with the study of Zhao et al ( 2023 ), who found that water availability had a significant positive effect on the establishment rate of ragweed. We found that the highest rainfall total since 2002 (SHMÚ): 493.2 mm in 2018 (Bratislava) and 600.7 mm in 2010 (B. Bystrica) led to a significant shift in the onset of the Ambrosia pollen season (up to 22 days earlier).…”
Section: Discussionsupporting
confidence: 93%
“…In the invasive species Ambrosia artemisiifolia which reacts favourably to a warmer climate, the earlier onset of flowering is related to precipitation pre-season, in the period from sprouting to pollen maturation. This is in line with the study of Zhao et al ( 2023 ), who found that water availability had a significant positive effect on the establishment rate of ragweed. We found that the highest rainfall total since 2002 (SHMÚ): 493.2 mm in 2018 (Bratislava) and 600.7 mm in 2010 (B. Bystrica) led to a significant shift in the onset of the Ambrosia pollen season (up to 22 days earlier).…”
Section: Discussionsupporting
confidence: 93%